Survey of Volunteer Activity, 1987 [Canada]: Volunteer File - Statistics Canada. Special Surveys Group (Borealis, 1990)
The Survey of Volunteer Activity (VAS) was undertaken by Statistics Canada to profile the characteristics of individual volunteers. This survey provides previously unavailable information regarding the activities of volunteers, the organizational settings in which these activities take place, reasons for becoming volunteers, the amount and pattern of time spent on these activities, the cost of volunteering as well as personal opinions on aspects of voluntary experience. The Volunteer File contains data used to estimate characteristics of volunteers such as motivation of volunteers to participate in volunteer activities. The Survey of Volunteer Activity was conducted as a supplement to Statistics Canada's November 1987 Labour Force Survey (LFS). Coverage includes all Canadian individuals aged 15 and over excluding residents of the Yukon and Northwest Territories, inmates of institutions, full-time members of the Canadian Armed Forces and residents of Indian reserves.